Theoretical and experimental analysis of open-slotted axial-flux permanent magnet electrical machine - (:unkn) unknown (SILA SCIENCE, 2012)
This paper presents an open-slotted axial-flux permanent magnet (AFPM-OS) machine design, magnetic analysis, and experimental study. In the literature, torus type axial-flux permanent magnet machines usually have closed slots. In this study, the open-slotted structure provides ease of construction and the rotor structure is composed of a rectangular magnet instead of trapezoidal magnets, which reduces construction costs. The suitability of the changed design is proven based on experimental results.
Keywords: Axial flux machines; Open slots; TORUS; Finite element analysis; COGGING TORQUE; DESIGN